Seismic Domain Identification Algorithm Using Fuzzy Logic Methods With Combined Geological and Geomorphological Data for the Case of Sakhalin Island - Sobisevich Aleksey; Steblov G. M.; Agibalov A. O.; Aleshin Igor; Balashov G. R.; Kondratov A. D.; Makeev V. M.; Perederin V. P.; Perederin F. V.; Sentsov A.; Kholodkov Kirill I. (Russian Journal of Earth Sciences)
An algorithm for identifying seismic generation zones or “seismic domains” using fuzzy logic has been developed and tested on the island of Sakhalin. Initial data were obtained from diagrams of the distribution of “weak” zones, relief elevation distribution skewness, and magnitude of recent area deformation for one year. These data were processed using a γ-operator in fuzzy logic with γ = 0.9, which allowed us to identify areas with high seismic activity. The areas where these active areas intersect with zones with increased compressive stress values, as determined by computer modeling, were considered to be seismic zones. It was shown that, if there are not enough source materials available, it is possible to exclude information about the recent deformation field from consideration and use an assumed grid of active faults for computer modeling. This approach may be useful when analyzing areas that have not been studied well.